Risk indicators for oral ulcers among people living with HIV during the first wave of the pandemic: a cross sectional study - Morenike Oluwatoyin Folayan; Roberto Ariel Abeldaño Zuñiga; Jorma I. Virtanen; Nourhan M. Aly; Oliver C Ezechi; Joanne Lusher; Maha El Tantawi; Annie L Nguyen (BMC, 2023)
Abstract Background Little is currently known about HIV-related parameters that may increase the risk for oral ulcers during the COVID-19 pandemic. This study aimed to overcome this gap in research by assessing the associations between HIV viral load, antiretroviral adherence profile, co-morbidity status, SARS-CoV-2 infection and oral ulcers among people living with HIV (PLHIV). Methods This was a secondary analysis of data generated from 21,206 to 18 years and above, recruited from 152 countries through an online survey between July and December 2020. Data were extracted for 874 people who reported living with HIV. The dependent variable was reporting having oral ulcer. The independent variables were the viral load, adherence to antiretroviral treatment and a history of SARS-CoV-2 infection. The confounding variables were age at last birthday and sex at birth. A multivariable logistic regression analysis was conducted to determine the associations between the dependent and independent variables after adjusting for the confounding variables. Results Of the 874 participants, 99 (11.3%) reported having oral ulcers during the first wave of the COVID-19 pandemic. The odds of PLHIV having oral ulcers during the first wave of the COVID-19 pandemic was significantly higher for people who did not know their viral load than those who had undetectable viral load (AOR: 2.036; 95% CI: 1.204-3.443; p = 0.008); and people who did not adhere to the use of antiretroviral treatment than those who adhered (AOR: 4.113; 95% CI: 2.567-6.589; p < 0.001). Also, PLHIV who had SARS-CoV-2 infection had significantly higher odds of having oral ulcers than those who did not have the infection (AOR: 14.556; 95% CI: 4.500-47.078; p < 0.001). PLHIV who had co-morbidities had non-significantly higher odds of having oral ulcers than those without co-morbidities (AOR: 1.170; 95% CI: 0.656-2.085; p = 0.595). Conclusion Oral ulcers may be an indicator of poor adherence to antiretroviral therapy and unsuppressed viral load among PLHIV. It may also be an indicator of SARS-CoV-2 infection and a signal to take prompt and critical care of affected individuals because of the risk for severe COVID-19 for these individuals.